Induksi Embriogenesis Somatik Dendrobium mussauense melalui Teknik Thin Cell Layer (TCL) dengan Penambahan 2,4-D - Noli, Zozy Aneloi; Suwirmen; Dinya Khairani Aisa Tumanggor (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2025)
In vitro culture provides an effective strategy for conserving and mass propagating the endangered orchid Dendrobium mussauense. This study aimed to evaluate the effects of different concentrations of 2.4-D on somatic embryogenesis (SE) induction using transverse thin cell layer (TCL) and non-TCL techniques. A factorial Completely Randomized Design (CRD) was employed, involving two factors: culture technique (TCL and non-TCL) and 2.4-D concentrations (1, 2, 3, and 4 mg L-¹), with four replications for each treatment. Explants were stem segments from 12-month-old D. mussauense plantlets. The highest survival and SE formation rates were observed in non-TCL explants treated with 4 mg L⁻¹ 2.4-D, reaching 75% and 50%, respectively. The earliest shoot and root emergence occurred at 13–14 and 23–25 days, respectively, under the same treatment. SE development in non-TCL explants treated with 2 mg L⁻¹ 2.4-D progressed through globular, scutellar, and coleoptilar stages within two weeks. Overall, 2.4-D concentrations of 2 and 4 mg L-¹ were most effective for SE induction in D. mussauense using both TCL and non-TCL techniques. Keywords: auxin, explant, SE, root induction, shoot induction.